Treatment patterns and outcomes in goblet cell carcinoid tumors of the appendix. Issue 7 (8th October 2019) - Fields, Adam C.; Lu, Pamela; Enzinger, Andrea; Goldberg, Joel; Irani, Jennifer; Bleday, Ronald; Nash, Garrett; Melnitchouk, Nelya
Abstract: Background: Goblet cell carcinoid (GCC) tumors of the appendix are a rare malignancy. We aim to examine the overall survival per stage and the relationship between different treatment modalities and outcomes for patients with GCC tumors of the appendix. Methods: We identified patients with GCC tumors of the appendix from the National Cancer Database. The main outcome was overall patient survival and cox proportional hazard models were used to ascertain predictors of survival. Results: There were 2552 patients identified. The median age of diagnosis was 57 (interquartile range: 49‐65) and 52.3% of patients were female. The 5‐year survival for Stage I disease was 91.1% (95% confidence interval [CI]: 82.2%‐95.7%), for Stage II disease was 90.5% (95% CI: 85.8%‐93.7%), for Stage III disease was 57.0% (95% CI: 45.0%‐67.3%), and for Stage IV disease was 18.9% (95% CI: 9.3%‐31.0%). In a Cox proportional hazard model, older age (hazard ratio [HR]: 1.1; 95% CI: 1.03‐1.12; P < .001), lymph node metastasis (HR: 6.9; 95% CI: 2.76‐17.01; P < .001), and positive surgical margins (HR: 2.9; 95% CI:1.13‐7.26; P = .003) were associated with worse overall survival for Stages I to III disease while only older age (HR: 1.03; 95% CI: 1.002‐1.06; P = .04) was associated with worse overall survival for Stage IV disease. Conclusions: Patients with GCC tumors of the appendix who have the nonmetastatic disease have a high 5‐year survival. We have identified several prognostic factors for GCC.